1981
DOI: 10.1073/pnas.78.11.7010
|View full text |Cite
|
Sign up to set email alerts
|

Base-pair substitution hotspots in GAG and GCG nucleotide sequences in Escherichia coli K-12 induced by cis-diamminedichloroplatinum (II).

Abstract: Cell killing and mutation induction by cis-and trans-Pt(NH3)2Cl2 in Escherichia coli were examined by studying forward mutagenesis in the lad gene in cells with different repair capacities. Survival experiments showed that repair-proficient cells were slightly more sensitive for the cis isomer than for the trans isomer, whereas repair-deficient RecA and UvrB cells were extremely sensitive only for the cis compound. cis-Pt(NH3)2CI2 induced mutagenesis in both wild-type cells and RecA cells but not in UvrB cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(59 citation statements)
references
References 41 publications
2
56
0
1
Order By: Relevance
“…We found that all four dNTPs (lane 2) extend the substrate at only some sites and to lesser degree than in the presence of Mn (dimer position [35][36]. dATP is preferentially incorporated at some sites to a greater extent than with all four dNTPs present (dimer position [35][36]. Some insertion of dGTP occurs (dimer position 32-33); however, the extent is less and the number of sites is fewer than with dATP, as shown by the results in the presence of Mg2+ given in Table 1.…”
Section: Identification Of Nucleotides Inserted Opposite Pyrimidinementioning
confidence: 83%
“…We found that all four dNTPs (lane 2) extend the substrate at only some sites and to lesser degree than in the presence of Mn (dimer position [35][36]. dATP is preferentially incorporated at some sites to a greater extent than with all four dNTPs present (dimer position [35][36]. Some insertion of dGTP occurs (dimer position 32-33); however, the extent is less and the number of sites is fewer than with dATP, as shown by the results in the presence of Mg2+ given in Table 1.…”
Section: Identification Of Nucleotides Inserted Opposite Pyrimidinementioning
confidence: 83%
“…The activity of cisplatin is closely related to its binding to DNA (35). Highly conclusive evidence for this target was the early observation that cells deficient in DNA repair are hypersensitive to cisplatin (36,37), suggesting that cisplatin and other drugs bind DNA. Early studies showed that of the four bases the N7 site of guanine is strongly preferred (see also Fig.…”
Section: Recent Mechanistic Insights For Cisplatinmentioning
confidence: 99%
“…cis-DDP, on the other hand, binds covalently to DNA. Attachment of cis-DDP to poly(dG) regions through intrastrand crosslinking of guanosine N7 atoms is thought to be responsible for its various biological activities (13)(14)(15)(16)(17) DNA-Drug Reactions and Analysis. Reaction samples containing the 165-bp 32P-labeled DNA piece and sonicated calf thymus carrier DNA (1 mg/ml) were incubated with cis-or trans-DDP at a drug-to-nucleotide (D/N) mole ratio of 0.33, 0.165, 0.083, or 0.041 in 1 mM sodium phosphate/5 mM sodium chloride buffer, pH 7.4, at 37°C for 3 hr.…”
mentioning
confidence: 99%
“…cis-DDP, on the other hand, binds covalently to DNA. Attachment of cis-DDP to poly(dG) regions through intrastrand crosslinking of guanosine N7 atoms is thought to be responsible for its various biological activities (13)(14)(15)(16)(17). Previously we showed that the intercalating drug ethidium bromide changes the nuclease-sensitive DNA-binding sites of cis-DDP (15) and that ethidium bromide, distamycin A, and actinomycin D modify the sequence-specific cleavage mode of bleomycin (18 (14).…”
mentioning
confidence: 99%